Incidence and risk factors for central nervous system relapse in patients with primary mediastinal large B‐cell lymphoma in the rituximab era. Issue 1 (8th December 2022) - Vassilakopoulos, Theodoros P.; Panitsas, Fotios; Mellios, Zois; Apostolidis, John; Michael, Michalis; Gurion, Ronit; Ferhanoglu, Burhan; Hatzimichael, Eleftheria; Karakatsanis, Stamatios; Dimou, Maria; Kalpadakis, Christina; Katodritou, Eirini; et al.
Abstract: Central nervous system (CNS) involvement is rare in primary mediastinal large B‐cell lymphoma (PMLBCL). We aimed to evaluate the incidence of CNS relapse as first treatment failure event and the effect of the induction chemotherapy regimen, central nervous system ‐ international prognostic index (CNS‐IPI) and other clinical and laboratory variables on the risk of CNS relapse in 564 PMLBCL patients treated with immunochemotherapy. Only 17 patients (3.0%) received CNS prophylaxis. During a 55‐month median follow‐up only 8 patients experienced CNS relapse as first event, always isolated. The 2‐year cumulative incidence of CNS relapse (CI‐CNSR) was 1.47% and remained unchanged thereafter. The CI‐CNSR was not affected by the chemotherapy regimen (R‐CHOP or R‐da‐EPOCH). None of the established International Prognostic Index factors for aggressive lymphomas predicted CNS relapse in PMLBCL. The 2‐year CI‐CNSR in patients with versus without kidney involvement was 13.3% versus 0.96% ( p < 0.001); 14.3% versus 1.13% with versus without adrenal involvement ( p < 0.001); and 10.2% versus 0.97% with versus without either kidney or adrenal involvement. CNS‐IPI was also predictive (2‐year CI‐CNSR in high‐risk vs. intermediate/low‐risk: 10.37% vs. 0.84%, p < 0.001). However, this association may be driven mainly by kidney and/or adrenal involvement. In conclusion, in PMLBCL, CNS relapse is rare and appears to be strongly associated with kidney and/or adrenal involvement.